Cultural Da’wah Strategies In Religious Tourism: A Symbolic Interactionist Analysis At The Pilgrimage Site Of Sunan Kalijaga - Aisyah Astinadia Siregar (INJECT (Interdisciplinary Journal of Communication), 2025)
This study explores cultural da’wah communication practices in religious tourism, specifically at the Sunan Kalijaga pilgrimage site in Demak, Central Java. Using a qualitative approach with in-depth interviews and observation, the research investigates how religious messages are conveyed by caretakers and guides to pilgrims. The findings reveal that da’wah is presented through symbolic narratives, traditional rituals, and local cultural expressions, fostering inclusive spiritual experiences. This study highlights religious tourism as a potential medium for non-confrontational and contextual da’wah communication, relevant for diverse audiences.